Mapping Evidence of Pharmacy Services for COVID-19 in China - Yi, Zhan-Miao; Hu, Yang; Wang, Guan-Ru; Zhao, Rong-Sheng (Frontiers in Pharmacology, 2020)
Objective: To explore the role of pharmacists and innovation of pharmacy interventions for COVID-19 patients.We comprehensively searched PubMed and Chinese databases Sinomed, China National Knowledge Infrastructure to identify studies reporting pharmacist interventions and pharmacy services for COVID-19 patients using a predefined search strategy. The search period was from inception to April 2020. We also manually searched the reference list of included studies and websites of important journals.Results: A total of 156 studies were identified by applying the search criteria. After screening, 91 studies with the majority are reviews (n=77, 84.62%) published in Chinese (n=83, 91.2%) were included. Pharmacist interventions for COVID-19 patients most commonly related to guideline or consensus development (n=10, 10.98%), emergency supply (n=10, 10.98%), formulating prevention and control strategies (n=14, 15.39%), service model innovation (n=14, 15.39%), traditional pharmaceutical care services (n=39, 42.86%) and retrospective analysis of treatment regimens (n=4, 4.40%).Pharmacy services have an important role in the COVID-19 pandemic control.However, more original research, especially outcome evaluation and real-world data analysis, is needed to provide valid and reliable ways for curbing this pandemic.